Exploring the pharmacological mechanism of compound kushen injection in the treatment of breast cancer using in vitro experiments: Coupling network pharmacology with GEO database - Ye, Yong; Zhang, Bo; Liang, Qiuyun; Wang, Dandan; Bai, Facheng; Li, Yuanhong; Wei, Lizhi; Li, Lilan; Huang, Huixue; Tang, Yunxia (Frontiers in Oncology, 2022)
Background: Breast cancer (BC) is one of the most common malignant tumors in women and poses a serious threat to their health. Compound Kushen injection (CKI) has shown therapeutic effects on a variety of cancers, including BC, and it can significantly improve the lives of patients. However, the underlying mechanism remains unclear and needs to be fully elucidated. Methods: The active constituents of CKI were identified through a literature review, and the anti-BC targets of CKI were determined using multiple databases and a ChIP data analysis. Subsequently, the target was analyzed on the DAVID database through GO and KEGG to identify the key pathway that CKI affects to exhibit anti-BC activity. In addition, MCF-7 and MDA-MB-231 cells were treated with CKI for 24 and 48 hours at five concentrations, and the effects of CKI on cell proliferation and apoptosis were measured using MTT and annexin V/propidium iodide staining assays, respectively. The genes identified to be involved in this pathway were verified using real-time quantitative PCR (qPCR) in BC cells. Results: Twelve CKI anti-BC targets were obtained by a comprehensive analysis of the targets collected in the databases and results from the ChIP analysis. Bioinformatics analysis was performed for 12 targets. KEGG analysis showed that the 12 targets were mainly related to the VEGF, ErbB, and TNF signaling pathways. We focused our study on the VEGF signaling pathway as the p-value for the VEGF signaling pathway was the lowest among the three pathways. In vitro experiments showed that CKI significantly inhibited the proliferation of BC cells and induced apoptosis. Furthermore, qPCR and WB experiments showed that the expression of the PIK3CA, SRC, and NOS3 genes involved in the VEGF signaling pathway in BC cells increased after CKI intervention. Conclusion: CKI significantly inhibited the proliferation of BC cells and induced apoptosis. The main mechanism for the anti-BC effect of CKI may be that it regulates the VEGF signaling pathway by increasing the expression of PIK3CA, SRC, and NOS3. Macrozamin and lamprolobine may be the main active components of CKI against BC.